2017
DOI: 10.1002/mabi.201600518
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Nano‐Prodrug Platform with Reactive Drug Loading, Superb Stability, and Fast Responsive Drug Release for Targeted Cancer Therapy

Abstract: Nano-prodrugs usually involve a multistep synthesis which largely compromises their benefits. Here, a smart nano-prodrug platform with reactive drug loading, superb stability, and triggered drug release is reported for targeted melanoma therapy. cRGD-decorated polymersomal mertansine prodrug (cRGD-PS-DM1) is readily fabricated from cRGD-functionalized poly(ethylene glycol)-b-poly(trimethylene carbonate-co-dithiolane trimethylene carbonate) with simultaneous loading of mertansine (DM1) via thiol-disulfide excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…The cRGD-decorated polymersomal mertansine prodrug (cRGD-PS-DM1) has been readily fabricated from cRGD-functionalized poly(ethylene glycol)- b -poly(trimethylene carbonate- co -dithiolane trimethylene carbonate) with simultaneous loading of mertansine (DM1) via thiol-disulfide exchange reaction and disulfide cross-linking of polymersomal membrane. The study showed that cRGD-PS-DM1 has high drug loading, superior stability, and fast responsive drug release 156 .…”
Section: Emerging Techniques For Drug Deliverymentioning
confidence: 97%
See 1 more Smart Citation
“…The cRGD-decorated polymersomal mertansine prodrug (cRGD-PS-DM1) has been readily fabricated from cRGD-functionalized poly(ethylene glycol)- b -poly(trimethylene carbonate- co -dithiolane trimethylene carbonate) with simultaneous loading of mertansine (DM1) via thiol-disulfide exchange reaction and disulfide cross-linking of polymersomal membrane. The study showed that cRGD-PS-DM1 has high drug loading, superior stability, and fast responsive drug release 156 .…”
Section: Emerging Techniques For Drug Deliverymentioning
confidence: 97%
“…Prodrug nanomedicine self-assembled by amphiphilic prodrug usually achieves high drug loading and stability153, 155, 156. pH-responsive micellar nanoparticles are prepared by self-assembly of an amphiphilic poly(ethylene glycol)-acetal-paclitaxel (PEG-acetal-PTX) prodrug, and free PTX can be encapsulated in the hydrophobic core of the nanoparticles.…”
Section: Emerging Techniques For Drug Deliverymentioning
confidence: 99%
“…Nanoformulation of prodrugs, a combination of prodrug strategy and nanotechnology tactics, inherits the merits both hence holds a few advantages, such as high drug loading efficiency, improved drug availability and enhanced accumulation in cancer cells in terms of drug delivery. Reactive drug loading, decent stability, and triggered drug release and targeted therapy [ 250 ] are the four essential components of a smart nanoprodrug platform and should improve the pharmacokinetics and decrease toxicity of the chemotherapeutic by transforming an encapsulated prodrug to tumor sites, where it is selectively released and converted to active parent drug.…”
Section: Remark and Outlookmentioning
confidence: 99%
“…The confocal microscopy studies have shown active tumor-targeting by cRGD-decorated nanoparticles to α v β 3 integrin overexpressing melanoma cells. In vivo experiments revealed a significant tumor growth inhibition with cRGD-functionalized nanoparticles loaded with mertansine when compared with non-targeting nanoparticles loaded with drug and free mertansine [116]. Another well-known receptor-mediated tumor-targeting moiety is folic acid.…”
Section: Redox-responsive Apc Nanocarriersmentioning
confidence: 99%